Olfactory impairment in patients with coronavirus disease 2019 self-perceived as asymptomatic. Issue 2 (26th February 2023) - Zahedi, F D; Husain, S; Wan Hamizan, A K; Tuang, G J; Gendeh, H S; Oui, T J; Mustafa, N; Kok, H T
Abstract: Background: Olfactory impairment may be present among patients with coronavirus disease 2019 self-perceived as asymptomatic. This study aimed to assess olfactory function among these individuals. Methods: A cross-sectional study involving patients with coronavirus disease 2019 self-perceived as asymptomatic was conducted. Assessments included the subjective Malaysian Smell and Taste Questionnaire and the culturally adapted Malaysian version of the objective Sniffin' Sticks Identification smell test. Results: In 81 participants (mean age of 31.59 ± 12.04 years), with mean time from diagnosis to smell test of 7.47 ± 3.79 days, subjective assessment showed that 80.2 per cent were asymptomatic (questionnaire score of 6) and 19 per cent had mild symptoms (questionnaire score of 7 and 8). The mean objective smell test score was 10.89 ± 2.11. The prevalence of olfactory impairment was 76.6 per cent among patients with coronavirus disease 2019 self-perceived as asymptomatic. There was no association between the questionnaire and the smell test scores ( p = 0.25). There was a correlation between the smell test score and the duration from diagnosis to smell test ( p = 0.04). Conclusion: The objective assessment demonstrated that coronavirus disease 2019 patients who perceived themselves as asymptomatic showed olfactory impairment.